The incentive gap: LULUCF and the Kyoto mechanism before and after Durban. Issue 6 (31st December 2012) - Ellison, David; Petersson, Hans; Lundblad, Mattias; Wikberg, Per‐Erik
Abstract: To‐date, forest resource‐based carbon accounting in land use, land use change and forestry (LULUCF) under the United Nations Framework Convention on Climate Change (UNFCCC), Kyoto Protocol (KP), European Union (EU) and national level emission reduction schemes considers only a fraction of its potential and fails to adequately mobilize the LULUCF sector for the successful stabilization of atmospheric greenhouse gas (GHG) concentrations. Recent modifications at the 2011 COP17 meetings in Durban have partially addressed this basic problem, but leave room for improvement. The presence of an Incentive Gap (IG) continues to justify reform of the LULUCF carbon accounting framework. Frequently neglected in the climate change mitigation and adaptation literature, carbon accounting practices ultimately define the nuts and bolts of what counts and which resources (forest, forest‐based or other) are favored and utilized. For Annex I countries in the Kyoto Mechanism, the Incentive Gap under forest management (FM) is significantly large: some 75% or more of potential forestry‐based carbon sequestration is not effectively incentivized or mobilized for climate change mitigation and adaptation (Ellison et al . 2011a). In this paper, we expand our analysis of the Incentive Gap to incorporate the changes agreed in Durban and encompass both a wider set of countries and a larger set of omitted carbon pools. For Annex I countries, based on the first 2 years of experience in the first Commitment Period (CP1) we estimate the IG in FM at approximately 88%. Though significantly reduced in CP2, the IG remains a problem. Thus our measure of missed opportunities under the Kyoto and UNFCCC framework – despite the changes in Durban – remains important. With the exception perhaps of increased energy efficiency, few sinks or sources of reduced emissions can be mobilized as effectively and efficiently as forests. Thus, we wonder at the sheer magnitude of this underutilized resource.